Telaah Sanad dan Matan Hadis Iftirāq al-Ummah - Mardiyah; Alma’arif; Abdul Wahab; Sari Haryati (Kartika: Jurnal Studi Keislaman, 2026)
The Hadith of Iftirāq al-Ummah states that the Muslim community will split into seventy-three sects, with only one group known as al-Firqah al-Nājiyah attaining salvation. This study aims to critically analyze the chain of transmission (sanad) and the text (matan) of this hadith, as well as to examine its contemporary theological implications, particularly concerning the understanding of the Firqah Nājiyah concept within the framework of Religious Moderation. The methodology applied includes takhrij and naqd al-ḥadīth (hadith criticism), enriched by a comparative study of the perspectives of classical theologians (mutakallimūn) and contemporary Indonesian scholars. The research findings reveal that this hadith possesses a strong sanad (ṣaḥīḥ li-ghayrihi) due to support from various corroborative transmissions (mutāba'āt). However, the matan specifically the threatening phrase "Hellfire" is vulnerable to criticism of shudhūdh if interpreted literally and outside its proper context. Within the contemporary socio-religious context of Indonesia, thinkers and scholars reconstruct the meaning of al-Firqah al-Nājiyah not as an exclusive and closed group identity, but as a collective commitment to practicing the principles of Religious Moderation (al-Wasaṭiyyah) and maintaining Unity (al-Jamā'ah). This reinterpretation ultimately encourages the development of an attitude of inclusiveness, tolerance, and broader social harmony within a plural society